Analisis Konflik Batin Tokoh Utama dalam Novel “Rumah Untuk Alie” Karya Lenn Liu - Zahrah, Nafysah; Kasmantoni; Friantary, Heny (Universitas Al-Qolam Malang, 2025)
This study discusses the inner conflict of the main character in the novel Rumah Untuk Alie by Lenn Liu. The purpose of this study is to describe the form of inner conflict experienced by the main character, and to analyze the factors that cause the emergence of the conflict based on the theory of basic human needs. The method used in this study is a qualitative method with a literature study technique. The data sources in this study are quotations in the novel that describe the mental condition of the main character, while the data is analyzed based on the theory of inner conflict from Muis and Abraham Maslow's hierarchy of needs. The results of the study show that the character Alie experiences various forms of inner conflict that are manifested in the emotions of depression, anxiety, anger, and frustration. These conflicts are rooted in the unfulfilled basic needs in her life, especially the need for security, belonging and love, and the need for self-esteem. The mistreatment of her father and four siblings after the death of her mother was the main factor that triggered the destruction of Alie's psychological condition. This pressure caused Alie to lose her emotional shelter, feel alienated in the midst of her own family, and question the value of her existence in the world. This research is expected to provide a deeper understanding of how the inner dynamics of a character in a literary work represent human psychological reality, while enriching the study of literary psychology.